Financial Inclusion and Economic Growth in Sub-Saharan Africa: A Panel ARDL and Granger Non-Causality Approach - Oyelowo, Oyelude Yekeen; Afolabi, Babatunde; Balogun, Adekunle Alexander; Oyamendan, Anthony; Olanipon, Olaoluwa Omotayo; Olokor, Chukwuemeka; Ebhoaye, Solomon Ogiedo (Acta Universitatis Danubius. Œconomica, 2024)
The study examines the impact of financial inclusion on economic growth in sub-Saharan Africa from 2010-2022. The correlation analysis revealed that all coefficients of the variables were below 0.8, indicating an absence of multicollinearity issues. However, the cross-sectional dependency test findings indicated interdependence among the nations studied. Subsequently, a second-generation unit root test was employed to assess the stationarity of the variables. The unit root test revealed a mixed level of stationarity among the variables. Utilising the Augmented Mean group approach, it was found that GDPCPS, NAC, NBR, NAT, and DAT positively correlated to economic growth in the region. Conversely, POP, TOT, and INF are negatively related to economic growth. The causality test also revealed bi-directional causality between NAC and GDPGR, NBR and GDPGR, BRA and GDPGR, INF and GDPGR, and POP and GDPGR variables. At the same time, there is uni-causality between NAT and GDPGR, DAT and GDPGR, GDPCPS and GDPGR, TOT and GDPGR. In response to our findings, the study recommends that the government and policymakers in SSA formulate policies to ensure that all the proxies of financial inclusion are expanded as they all trigger economic growth.